The impact of PDS partnerships in challenging times - Hill, Pixita del Prado; Garas-York, Keli; Ferrara, JoAnne, 1955-; Nath, Janice L. (Research in professional development schools, 2021)
"The Impact of PDS Partnerships in Challenging Times is the follow up to Doing PDS: Stories and Strategies from Successful Clinically Rich Practice (2018). The first book included stories that described our experiences across more than twenty-five years of PDS partnerships. We sought to examine and chronicle the innovative ways we negotiate school-university collaboration while explaining the development of the SUNY Buffalo State PDS consortium. This second volume strives to explore the impact of our endeavors individually at each school/community site and collectively as an entire consortium to point to the important ways that school-university partnership contributes to all stakeholders and where we might do better. SUNY Buffalo State's PDS roots go back to 1991 with one local school partner. Today this school-university partnership consortium connects with over 100 schools with approximately 45 signed agreements each semester in Western New York, nationally, and internationally. The SUNY Buffalo State PDS consortium is grounded in three frameworks for clinically rich practice: (a) the National Association for Professional Development Schools Nine Essentials (Brindley, Field, & Lesson, 2008); (b) CAEP Standards for Excellence in Educator Preparation, Standard 2 (http://caepnet.org/standards/standard-2, 2018); and (c) the Buffalo State Teacher Education Unit Conceptual Framework (https://epp.buffalostate.edu/conceptual-framework, 2018). Through specific examples, each chapter utilizes a case study approach to describe the nature of various partnerships situated in research with a focus on the impact of the partnership. The chapters are intentionally succinct to provide a focused look at a particular partnership activity as each contributes to the larger goals of the entire consortium. Every chapter follows a similar structure - defining a challenge identified by the members of the consortium, a review of the relevant literature, an explanation of how the school/community liaison team responded to the challenge and the data gathered to determine impact, an "impact at a glance" chart to report the findings, and an identification of the necessary next steps in the project"--